Business in great waters : the U-boat wars, 1916-1945 - Terraine, John. (London : Wordsworth Editions, 1999)
Twice within 25 years Britain was threatened with starvation by the menace of the U-Boat. In this study of submarine warfare, the author explains why Winston Churchill wrote "the only thing that ever frightened me during the war was the U-Boat peril". Until it had been overcome, the Anglo-American entry into Europe in 1944 would have been impossible. John Terraine concentrates on the combatants themselves, both German and Allied, but does not overlook the three main factors in the equation - the political, the military and the technological, as well as the intelligence, the weapons and the devices both sides employed in order to outwit each other. He also focuses on the fighting men on either side, seeing the action from "where it was at".
Originally published: London : L. Cooper, 1989.
Includes bibliographical references (pages 774-781) and index.
Keywords: 1900-1999; World War, 1914-1918 -- Naval operations -- Submarine; World War, 1914-1918 -- Naval operations, German; World War, 1939-1945 -- Naval operations -- Submarine; World War, 1939-1945 -- Naval operations, German; Submarines (Ships) -- Germany -- History -- 20th century; Military operations, Naval -- German; Military operations, Naval -- Submarine; Submarine warfare; Submarines (Ships); 2; Germany; History